2018
DOI: 10.1158/0008-5472.can-16-1701
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Adrenergic Signaling Promotes Intratumoral Innervation through BDNF Induction

Abstract: Mounting clinical and preclinical evidence supports a key role for sustained adrenergic signaling in the tumor microenvironment as a driver of tumor growth and progression. However, the mechanisms by which adrenergic neurotransmitters are delivered to the tumor microenvironment are not well understood. Here we present evidence for a feed-forward loop whereby adrenergic signaling leads to increased tumoral innervation. In response to catecholamines, tumor cells produced brain-derived neurotrophic factor (BDNF) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 22 publications
2
84
0
Order By: Relevance
“…We have shown that the ameloblastoma epithelium expresses detectable levels of the neurotrophins NGF and BDNF, as well as the neurotrophin receptors TRKA, TRKB, and P75/NGFR. Both NGF and BDNF have already been shown to promote tumor innervation in other tissues [29,72,74,79]. In addition to promoting cancer innervation, neurotrophin-mediated signaling has been shown to directly drive tumor onset and progression [72,74,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the ameloblastoma epithelium expresses detectable levels of the neurotrophins NGF and BDNF, as well as the neurotrophin receptors TRKA, TRKB, and P75/NGFR. Both NGF and BDNF have already been shown to promote tumor innervation in other tissues [29,72,74,79]. In addition to promoting cancer innervation, neurotrophin-mediated signaling has been shown to directly drive tumor onset and progression [72,74,[80][81][82].…”
Section: Discussionmentioning
confidence: 99%
“…In pancreatic (10) and gastric (28) cancers, where NGF production by cancer cells drives axonogenesis, the value of NGF as a prognostic biomarker should be investigated. In breast cancer, the expression of NGF is associated with lymph node invasion (30), and in ovarian cancer the production of BDNF drives adrenergic nerve infiltration (71). Therefore, given their role in tumor innervation, neurotrophic factors may be used as diagnostic and prognostic cancer biomarkers.…”
Section: Diagnostic and Prognostic Value Of Nerves And Neurotrophic Fmentioning
confidence: 99%
“…In addition to enhanced tumor angiogenesis, tumor innervation might further enhance tumorigenesis by enriching the tumor microenvironment with catecholamines released by the newly formed nerve endings. We and others have found that in response to catecholamines, tumor cells release neurotrophins (BDNF/NGF), which leads to increased tumor innervation and growth in restraint stress tumor models [59, 60]. There is evidence to show that behavioral stress contributes to an increase in catecholaminergic nerve fibers within lymphoid organs in primates, an indication of a long-term regulatory influence of stress on immune responses [61].…”
Section: Stress Inflammation and The Role Of Eicosanoidsmentioning
confidence: 99%